Tanggung Jawab Direksi terhadap Kerugian Kreditur dalam Kepailitan Perseroan Terbatas - Pahlevi, Muhammad Vito; Lie, Gunardi (Jurnal Sostekmas: Jurnal Sosial, Teknologi, dan Pengabdian Masyarakat, 2025)
The study's overarching goal is to draw conclusions on the kind and level of legal responsibility that limited liability company (PT) directors have toward creditors for losses sustained during a PT's insolvency. The organization's general direction, policy, and administration are determined by the board of directors, making it a crucial strategic organ. Directors, so long as they remain within their authority and behave with honesty, are often shielded from personal liability for business choices. Directors risk personal culpability in the event of insolvency due to their carelessness, abuse of authority, or unlawful activities. This paper examines the key provisions of two laws Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment and Law No. 40 of 2007 on Limited Liability Companies using a normative legal research approach. The concepts of corporate judgment rule and fiduciary duty are also examined. Directors' legal liability in bankruptcy safeguards creditors' interests and aids in holding management responsible and implementing good corporate governance (GCG), according to the results.